(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Soft-sediment deformation structures (SSD) are alterations produced almost simultaneously with sedimentation. They are directly related to internal characteristics of sedimentary materials as well as to external factors acting on them. Results derived from such alterations are evidenced as injections, fractures, volcanoes and convolute laminations, among other forms, affecting stratification either totally or partially. Soft-sediment deformation structures resulting from seisms are known as seismites. The present study aims at determining for the first time the presence of SSD structures in the Río Negro Formation, located in the northern area of San Matías Gulf, near Río Negro Lighthouse, Argentina (Fig. 1). To this end, structures were firstly identified and further described. Samples were subsequently collected for the determination of grain-size, mineralogy and organic matter content. Photographs of the different sectors evidencing deformations were taken in order to determine further comparative models. Morphology in the study area is associated to cliffs with vertical, fractured fronts and with an average height of 70 m in whose base torn-down blocks are accumulated. The geological structure of the study area is related to the Cuenca del Colorado and the Comarca Nordpatagónica, whose basement is mainly composed of Paleozoic and Mesozoic crystalline rocks. The sedimentary tertiary cover from the Miocene-Pliocene is represented by light-blue sandstones of the Río Negro Formation (Andreis, 1965). This unit was formed in an aeolian environment with intercalations of clay-silt shallow lagoons and a marine episode located in the mid area of the Río Negro Formation. At the top of the Río Negro Formation there are Pleistocene-Holocene sedimentites having a thickness of up to 5 m. Within the local structural framework of our study area there are fractures with a NE-SW and a NW-SE direction, which are related with fractures N55º, N90º and N350º azimuth located in the abrasion platform. According to Dzulinsky and Walton (1965), Lowe (1975), Brencley and Newall (1977), Clauss (1993), van Loon (2002), Owen (2003), Neuwerth et al. (2006), Alfaro et al. (2006), Montenat et al.(2007), among others (Table 1), and, taking into account the geometry of deformations, laboratory reconstructions and field observations from our study area, it can be concluded that the classifications of SSD structures tend to establish morphologic and genetic systematizations. The following characteristics were identified in our study area: limited deformations among stratigraphic horizons; a lateral continuity of SSD structures at considerable distances; and a confinement between non-deformed strata and its lithological association with psamitic-pelitic sediments. The study area, which is 4 km long and is located between Río Negro Lighthouse and the beginning of Banco Verde, is from the morphological point of view, a cliffed front with an ENE-WSW orientation. Different types of SSD structures were identified in this area. For example, from the morphological point of view and according to the loading mechanisms observed, simple-load structures (Fig. 2), attached and detached pseudonodules (Figs. 3, 4 and 5) and complex structures (Fig. 6) were identified. Furthermore, from the genetic point of view and according to the intrusion processes observed in soft sediments, water-escape structures (Fig. 7) and plate- or fountain-like deformations (Fig. 8) were found. From the genetic point of view, and based on the collapse and pressure mechanisms observed, basal slumping (Fig. 9) and directed-pressure structures (Fig. 11) were also found. The above-mentioned SSD structures were analyzed and interpreted following Strachan´s model (2002) (Fig. 10) and Laird´s model (1968) (Fig. 12). The origin of SSD structures depends on the characteristics of sedimentites and on the mechanisms that produce them. In the study area, the materials susceptible to deformation come from an interdune environment that is characterized by granulometric variations derived from the fluctuating and restrictive climatic conditions (Cojan and Thiry, 1992) that typify the Río Negro Formation. Fine-grained materials having low cohesion and poor sorting such as the sediments of deformed strata (Fig. 13) produced SSD structures as a result of high pore pressure and liquefaction effects (Tsuchida and Hayashi, 1971; Obermeier, 1996). Grain packing with a porous value as that allows intercommunication among grains and saturated material, is also crucial to the formation of SSD structures. The mineralogic content of deformed levels is composed of i) quartz, chalcedony, orthose, plagioclase, pyroxenes and biotite, opaques (magnetite and ilmenite, autigenic pyrite) in crystalline aggregates; ii) undetermined Fe oxides; and iii) colorless and light-brown unaltered volcanic glass shards, clays identified as smectite-illite interstratified and scarce kaolinite. Grains are mainly subangular and, to a lesser extent, sub-round and round. The surface of the majority of grains in the study area was found clean and with some marks. The percentage of CaCO3 was found to vary from 0.5 to 3% and that of total organic carbon (TOC) was found to reach 1.5%. Deformations may be produced as a result of load deformation mechanisms, fluid escape, basal slumping or pressure-directed displacements. Due to load deformation mechanisms, structures are linked to gravity-related movements occurring during the initial stages of deposition. For these deformations to occur, grain-size at the overlaying levels should be thicker than at the underlying levels, for example, sandstones rather than silstones or claystones. These deformations are related to water saturation at the deformed level (fluidization-liquefaction). Therefore, deformation mechanisms, which involve both expulsion and rotation of fragments as well as fluid escape, are characterized by the action of lithostatic pressure which produces movement (deformation) and by the action of the underlying sedimentary levels. Deformations may also result from a fluid escape mechanism, i.e., from a mechanism associated to i) the spatial arrangement of grains (packing), ii) their shape, iii) their tendency to inequigranularity, and iv) the communication among macro- and micro- pores as well as the high or low sinuosity connection among themselves (Net and Limarino, 2000). Further requirements for deformations to occur include particular thixotrophic conditions, especially the presence of colloids among grains. The rupture of unions of particles either by hitting or by shearing is, among others, a cause which produces an unbalance between hydrostatic pressure and lithostatic pressure. If the latter is altered, the energetic unbalance makes fine sediments flow among the weakly lithified sandstones whose extrusion will occur via both vertical and horizontal pore ducts (Lopez Gamundi, 1986; Clauss, 1993). Basal slumping produces deformations that are associated not only to soft sediments deposited in natural slopes but also to interbedded sand- and mud-levels. Layers tend to have a prismatic-shaped geometry whose materials are under ductile-to-fragile conditions, in which antique layers support younger ones. Once horizontality is affected, movement, which is marked by a rupture of the original slope, begins. The lower levels are expected to transport the upper ones without affecting the original succession of layers. At the delay of movement derived from the compressive effect of the displacement front, fluids extrude forming cones or cut dikes (Fig. 10). Several deformations of this type initiate movement as a result of differences in the hydrostatic gradient (Strachan, 2002). Deformations may be also produced as a result of pressure-directed displacements which are conditioned by the compaction level, thickness and ability of materials to deform. Thus, deformations occur because the original level is saturated in water as a result of the ductile behavior of materials (Bracco et al., 2005). Laird (1968) claims that SSD structures should meet some of the following requirements to be considered of seismic origin: slightly curved strata walls and floors to follow the original stratification and interruption of continuity of the stratum that is marked by a scar in which the sedimentary fillings keep their characteristics both above and below stratification. There could be rotated sediment clasts below the discontinuity as a result of a thrust-induced drag of the upper sedimentary packing. These processes could be, in turn, triggered either by the charge or pressure of the lithologic column, storm waves and seismicity. Storm-wave impact may also produce deformation in soft sediments. Nonetheless, no high energy structures such as cross-beddings or tsunami-type chaotic sedimentation were observed in our study area. Noteworthily, for stormwave-derived liquefaction to occur, waves should reach magnitudes higher than 6 m (Alfaro et al., 2002), this being a phenomenon that was not recorded in our study area. Taken together, findings from the present study indicate that SSD structures in our study area are seismic alterations that occurred in an event during the Andean cycle whose beginnings are traced approximately 45 My ago. The fact that i) both the roofs and bottoms of these structures are not associated to other processes of deformation, ii) their thickness does not exceed one meter, and iii) they are confined to a transitional area between the middle and top members of the Río Negro Formation, lying in some cases on claystones and in some other cases, on siltstones, originated in an interdune paleorelief, confirms their seismic origin.